Benefits of Peer Support in Online Japanese Breast Cancer Communities: Differences Between Lurkers and Posters - Setoyama, Yoko; Yamazaki, Yoshihiko; Namayama, Kazuhiro (JMIR Publications, 2011)
BackgroundWeb 2.0 has improved interactions among peers on the Internet, especially for the many online patient communities that have emerged over the past decades. Online communities are said to be particularly beneficial peer support resources for patients with breast cancer. However, most studies of online patient communities have focused on those members who post actively (posters), even though there are many members who participate without posting (lurkers). In addition, little attention has been paid to the usage of online communities among non-English-speaking patients. ObjectiveThe present study explored the differences in peer support received by lurkers and posters in online breast cancer communities. It also examined the effects of such support on both groups' mental health. MethodsWe conducted an exploratory, descriptive, cross-sectional, Web-based survey among members of four Japanese online breast cancer communities. In an online questionnaire, we asked questions regarding sociodemographics, disease-related characteristics, mental health, participation in online communities, and peer support received from those communities. ResultsOf the 465 people who accessed the questionnaire, 253 completed it. Of the respondents, 113/220 (51.4%) were lurkers. There was no significant difference between lurkers and posters with regard to sociodemographic variables. About half of the posters had been given a diagnosis of breast cancer less than a year previously, which was a significantly shorter period than that of the lurkers (P = .02). The 5 support functions extracted by factor analysis were the same for both posters and lurkers. These were emotional support/helper therapy, emotional expression, conflict, advice, and insight/universality. When the support scores were calculated, insight/universality scored highest for both posters and lurkers, with scores that were not significantly different between the two groups. Among the 5 support scores, emotional support/helper therapy and emotional expression were significantly higher among posters. For posters, emotional support/helper therapy and advice were negatively correlated with the anxiety subscale of the Hospital Anxiety and Depression Scale. Emotional expression, advice, and insight/universality were negatively correlated with the anxiety subscale for lurkers. ConclusionWe found that posters felt they received more benefits from online communities than lurkers did, including emotional support, helping other patients, and expressing their emotions. Yet even lurkers were found to gain a certain amount of peer support through online communities, especially with regard to advice and insight/universality. The results demonstrate that participation in online communities-even as a lurker-may be beneficial to breast cancer patients' mental health.